Revision of Tenomerga (Coleoptera, Cupedidae) of Japan and adjacent regions - Yoshitomi, Hiroyuki (Zootaxa, 2024)
Tenomerga Neboiss, 1984 distributed in Japan and its neighbouring countries is revised. Six species are recognized. Tenomerga anguliscutis (Kolbe, 1886) and T. trabecula Neboiss, 1984 are firstly recorded from Japan, and T. mucida (Chevrolat, 1844) is newly recorded from Taiwan.